Versatility of Zygomatic Implants in Dental Rehabilitation for Patients Following Partial or Total Maxillectomy Procedures: A Prospective Study - Devadoss, Pradeep; Prasad, T. Srinivasa; Kumar, J. Naveen; Jimson, S. (Journal of Neonatal Surgery, 2025)
Maxillary defects resulting from partial or total maxillectomy due to ablative surgeries for neoplasms or infections present multifactorial challenges involving function, esthetics, phonation, mastication, and psychological well-being. Restoration in such cases is often complex, particularly when conventional prosthodontic and implant rehabilitation is unviable due to extensive bone loss and compromised anatomy. Zygomatic implants provide a unique anchorage solution through engagement in the dense zygomatic bone, circumventing deficient or absent alveolar structures. This prospective clinical study was conducted at Meenakshi Ammal Dental College and Hospital and included 20 patients (12 males, 8 females) presenting with either severely atrophic posterior maxilla or post-maxillectomy defects. A total of 32 zygomatic implants were placed using a combination of virtual surgical planning, trans-sinus, and extramaxillary techniques. Parameters assessed included primary and secondary implant stability (RFA/ISQ), osseointegration, peri-implant soft tissue health, prosthesis retention, patient-reported outcome measures (PROMs), and radiographic marginal bone loss over a 36-month period. Outcomes revealed a 95% implant survival rate, with significant improvement in functional and psychosocial indices. The utilization of CBCT-based planning enhanced placement accuracy and reduced surgical complications. This study underscores the strategic role of zygomatic implants in rehabilitating maxillary defects, offering a predictable and long-term solution in advanced cases.